EFFECT OF CYCLIC LOADING ON THE CHANGE OF ROCK STRENGTH - Liffa Suci, Syani
Cyclic loading is the process of applying repeated load on rocks, such as from the utilization of heavy machinery and blasting in mine. Cyclic loading could affect the strength of rocks to the point of collapsing them. To be able to find out the effect of cyclic loading to rocks strength, research was done in the laboratory. The research was done by giving a cyclic loading on rocks sample made from Hung Ta Hydraulic Pressing Machine in the Laboratorium of Geomechanics and Mining Equipment, Bandung Institute of Technology. The amount of load that was given to the sample is 50% of initial unconfined compressive strength value (UCS), that is 5,12 MPa. The research was conducted to observe whether cyclic loading affects UCS value, Young's Modulus and Poisson's Ratio. The result of the research shows that UCS value decreases when subjected to cyclic loading. Cyclic loading also affects the Young’s Modulus value. The more cyclic is given, the smaller the Young’s Modulus value. Even though cyclic loading affects the UCS value and Young’s Modulus of rocks, it doesn't affect Poisson's Ratio.